The Examination of the Capacity of the Authorization in Establishing Right for the Authorized Person - Muhammad Salehi Mazandarani; Ali Javadieh (آموزه‌‌های فقه مدني)
The authorization which basically causes permissibility (Arabic: اباحه) for the authorized person has an unstable nature which with the revocation of the authorizer (in the condition of the absence of inability to revoke) and in any case with one of parties’ death or hajr (Arabic: حجر meaning: the interdiction upon the incompetent person) it is ended (terminated). Whereas it is necessary in some cases that the authorization coincides with the feature of continuance and it is not simply destroyed (ruined) which causes the loss of the authorized. With examining in the Articles of the civil code of Iran and the opinions of the law and fiqh scholars this importance is revealed that the authorization is able to establish right for the authorized. The important features of this authorization are: inability of the authorizer to terminate it, the continuation of the allowed authorization even in the situation of the parties’ death or hajr (Arabic: حجر meaning: the interdiction upon the incompetent person), the capability of forceable or voluntary transfer of the established right, … The recognition of such foundationary (ta’sisi) requires the authorization at least in cases which create right is supposed a legal act if not the legal presumption of the authorization will not go along with (will not be congruent with) the acceptance of acquiring right.